»Lige langt fra Militarismens overmodige Dasken paa Sabelskeden som fra Selvopgivelsens Jammerlighed« J.C. Christensen og dansk sikkerheds-, udenrigs- og forsvarspolitik 1901-09 - Christensen, Jens Ole (Historisk Tidsskrift, 2013)
J. C. Christensen and Denmark’s Security and Defence Policy, 1901-1909Since the late 1930s Danish historians have conventionally characterized Denmark’s security policy during the period between 1864, when it was defeated in war by Prussia and Austria, and 1949, when it became a member of NATO, as a policy of adaptation vis-à-vis Germany. It is perceived as stemming from both a sceptical attitude toward Danish military capability and a recognition of the limitations of small states. According to this interpretation foreign policy as well as defence policy were subordinated to adaptation. In 1990 Carsten Due-Nielsen questioned this conventional view in a new interpretation of the Estrup Government’s security policy from 1875 to 1894. He described it as a policy of balancing between the European Great Powers in an effort to sustain freedom of action. It was premised on a Danish military capability strong enough to deter an attack and, later perhaps, to enable Denmark to abandon its neutrality and ally itself with Germany’s opponents. Due-Nielsen thus calls into question whether the policy of adaptation can be seen as a constant trait in Danish security policy throughout the period. In his view the period was, on the contrary, characterized by competing policies of balance and adaptation: a competition that corresponded roughly to the political right and the left in domestic politics. After 1901, according to the conventional interpretation, Liberal Party governments (Venstre = the left) shifted to a more pronounced policy of adaptation towards Germany. The Liberals initiated a kind of no-defence strategy in which the role of the armed forces was not to defend the country against an opponent, but indirectly to support it by deterring other parties from gaining access to its land area and territorial waters. In this scheme neutrality became more flexible and less than even-handed. The security policy of the J. C. Christensen Government is cited as a particularly clear reflection of the German-oriented adaptation policy, carrying on, as it did, secret talks in 1906 and 1907 between L. C. F. Lütken, the top civil servant in the Danish Ministry of War, and the German Chief of Staff, Helmuth von Moltke. The conventional interpretation of the Lütken talks and Christensen’s security policy has its roots in the confrontational positions of the political parties of the time. Among historians hardly anyone has propounded the conventional view of the Liberals’ policy with greater impact than Troels Fink. The more general conventional view of adaptation as a constant in Danish security policy throughout the whole period from 1864 harmonizes conspicuously well with the security policy of the Social Liberal Party (Det radikale Venstre = the radical left) during the interwar years. Historical writing during these years interpreted the security policy of the past in the perspective of the party’s contemporaneous policy. A Social Liberal tradition was thus established and still remains relatively unchallenged. The present article is based, in part, on published as well as unpublished sources dealing with the conceptions of security and defence harboured by the military and the Liberal Party, and in part, on a new analysis of the core documents relating to the Lütken-Moltke talks. The study argues the case for a new interpretation of the Liberal governments’ alleged policy of German-oriented adaptation. The basis of the policy carried out by these governments was neither a sceptical attitude towards military capability nor the idea of accommodation as a natural consequence of Denmark’s small-state role after 1864. As a result, the question raised by Due-Nielsen as to whether adaptation was a common element of Denmark’s security policies throughout the whole 1864-1949 period is posed with further force. The article argues that the Liberals continued to balance between the Great Powers using Danish military strength as an important tool, and it argues against the view of a shift towards German-oriented adaptation. The centrepiece of the Christensen Government’s policy was a military capacity suited to the country’s marginal position between the Great Powers, which by no means entailed "an effective defence against all powers other than Germany," as Fink contended. Nor did the defence regulation of 1909 imply otherwise. There was no question of an anti-balance of power policy. It is likewise argued that the Lütken talks in no way involved an offer of alliance or other far-reaching elements of a rapprochement towards Germany. To the extent that one can speak of an accommodation with Germany, this was solely a matter of Denmark’s agreeing as far as possible to prevent any attempt to use Danish territory to launch an attack on Germany as well as an explicit rejection of the possibility of joining with Germany’s enemies. Likewise, there is reason to consider the conventional portrayal of the Christensen Government’s policy as rooted in historical writing inspired by Social Liberal views. In consequence, the article challenges the conception of a sharp break in Danish security policy when the Liberal majority in parliament took over the government in 1901. Despite disagreements between the conservative Right and the leftist Liberals on other issues, they did pursue similar security polices based on balancing between the Great Powers and a sufficiently strong military. The differences lay in means and circumstances. With regard to means, Estrup’s Conservative government was intent on the ability to resist in case of an overwhelming Great Power attack, while Christensen’s Liberal government was equally insistent on a military capability sufficient solely to ensure neutrality. The defining difference lay in Estrup’s will to resist, if security policy were to fail, and the country were forced to go to war. With regard to circumstances, the difference lay in international developments that brought Denmark into a marginal position, and Christensen saw this as opening new possibilities for pursuing a policy of neutrality. The dividing line between balance and adaptation policies lay not between the Conservatives and the Liberals, but between the Liberals and the Social Liberals. Taking that into consideration, the article argues that the real watershed in Danish security policy between, on the one hand, resistance or balance underpinned by military power and, on the other hand, adaptation devoid of military power should be fixed at about 1913-1914 at the time of Prime Minister Zahle’s second government and the outbreak of World War I. If we are looking for the moment of the most radical break in Danish security policy between 1864 and 1949, this is, no doubt, where to find it. Translated by Michael Wolfe